Analisis Potensi Dan Daya Dukung Sepanjang Jalur Ekowisata Hutan Mangrove Di Pantai Sari Ringgung, Kabupaten Pesawaran, Lampung - Yunita Sari; Slamet Budi Yuwono; Rusita Rusita (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Tourism is a potential sector that being developed in the province of Lampung. Mangrove forest in Sari Ringgung Beach (PSR) has a potential to be developed into ecotourism because it has a rich flora and fauna diversity that characterized by the increasement of visitors number. An increasing number of visitors be fearful could damage the mangrove forest. The aim of these research were to analyze the carrying capacity in mangrove ecotourism track and it is was conducted in February - March 2015. These research used survey method and data collection techniques used exploration method. Carrying capacity of ecoutourism area counted by DDK formula = K x Lp/Lt x Wt/Wp. The results of these research show that value of the carrying capacity was 87 visitors/day with potential in the form of 20 types of mangrove and fauna in the form of six species of birds. Keywords: ecotourism, carrying capacity, mangrove, sari ringgung beach